Critical Perspectives on Anti-Government Extremism - Ebbrecht, Christopher Kehlet (Perspectives on terrorism, 2024)
While the Global North is still facing the challenge of traditional forms of violent extremism (e.g. right-wing, left-wing, and militant Islamism), intelligence services and scholars alike have highlighted potential threats from novel extremist orientations that have (re) emerged over the past decade. One such variant is captured by the notion of anti-government extremism, which in its most simple form describes extremist attitudes or actions that oppose government and institutions of authority. In this research note, we offer critical perspectives on anti-government extremism as an analytical construct. Specifically, we raise questions concerning the extent to which the current definition of anti-government extremism always captures attitudes and/or actions that are indeed i) extremist, and ii) anti-governmental. We then discuss the implications and potential negative constitutive effects these unanswered conceptual issues may raise in relation to preventing and countering violent extremism (P/CVE), and conclude with a call for further debate and research on the theoretical and analytical merits of anti-government extremism.